Higher Preoperative Endometrial Cancer Risk Showed More Advanced Stage - Iskandar, Jasmine (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To evaluate the preoperative endometrial cancer risk as a guidance to choose the type of surgical approach based on European Society for Medical Oncology guideline (2009). Method: Cross-sectional study involved 73 endometrial cancer patients of Dr. Cipto Mangunkusumo Hospital, from January 2006 to December 2012 which obtained from medical record. The inclusion criteria were endometrial cancer patients with complete D&C, ultrasonographic, and postoperative histopathological reports. Endometrial cancer risk of recurrence was classified according to ESMO 2009 and final diagnosis and stage based on FIGO. Result: From 405 patients, only 73 patients had complete reports. Most of the them were postmenopausal (54.8%), non-nulliparity (79.9%), and obese (49.5%) women. According to risk of recurrence stratification, low, intermediate and high risk were found in 12 patients, 27 patients, and 34 patients. Based on FIGO, there were 60.2% early and 39.8% advanced stage. In high risk group, rates of advanced stage were prominent compared to other groups. There were 38.3% patients with postoperative positive lymph nodes metastases. Conclusion: Most of the endometrial cancer patients were preoperatively diagnosed as high risk. The commonest stage after surgical examination were IIIC. High risk of recurrence showed more positive lymph node compared to low or intermediate risk. Result of preoperative histopathological and myometrial invasion compared to postoperative results were showed to be inconsistent. Patients with â¥ 2 myometrial invasion had more positive lymph nodes metastases. Endometrial cancer risks compared to FIGO stage showed the higher the risk, the more advanced the stage were. [Indones J Obstet Gynecol 2014; 2: 99-105] Keywords: endometrial cancer, FIGO stage, high risk, histological type, intermediate risk, low risk, lymph node.